Professional learning as 'diffractive' practice: rhizomatic peer coaching. Issue 5 (2nd September 2016) - Charteris, Jennifer; Smardon, Dianne
Abstract: Acknowledging an abundance of technicist models for teacher continuing professional development (CPD), the authors draw from Deleuzoguattarian theory to frame peer coaching as rhizomatic practice. Rhizome theory enables engagement with the creative breaks and departures in peer coaching assemblages. Agentic and innovative teacher learning can occur when teachers can take lines of flight to think differently about their teaching practices. Deleuzoguattarian notions of rupturous lines signal teacher-generated possibilities for new initiatives. Located in an Aotearoa/New Zealand facilitated inquiry CPD context, the article explores how nine teachers engaged in a formal process of collaborative dialogue. A rhizomatic approach to dialogue encompasses a dynamic view of teacher learning. Openness to emergence can enable educators to theorise pedagogy creatively to potentiate a multiplicity of pathways forward.